Mirror Images in Different Frames? : Johor, the Riau Islands, and Competition for Investment from Singapore - Hutchinson, Francis E. (ISEAS monograph series., 2015)
In the early 1990s, Singapore, the Malaysian state of Johor, and the Riau Islands in Indonesia sought to leverage their proximity, differing factor endowments, and good logistics connections to market themselves as an integrated unit. Beyond national-level support in all three countries, the initiative had the support of state and provincial leaders in Johor and Riau, respectively. Now, however, the situation is markedly different. The Malaysian government and its Johorean equivalent have invested considerable resources in encouraging closer integration with Singapore. For its part, the Indonesian central government has been promoting special economic zones and export-oriented activities. However, the provincial government of the Riau Islands has turned away from export-oriented industrialization, preferring instead to promote cultural sub-nationalism and traditional economic activities such as fishing and small-scale farming.